EXPERIENCE WITH INTRAPERITONEAL CHEMOTHERAPY USING ASCITIC FLUID AS A SOLVENT OF CHEMICALS IN THE TREATMENT OF OVARIAN CANCER - Yu. S. Sidorenko; G. A. Nerodo; A. P. Menshenina; L. Yu. Golotina; N. D. Ushakova (Опухоли женской репродуктивной системы)
Thirty two with the ascitic form of Stages IIIC—IV ovarian cancer underwent 1 to 3 courses of intraperitoneal multidrug therapy using a protein ascitic fluid concentrate (PAFC) as a solvent of drugs (cisplatin, cyclophosphan, doxorubicin) according to the CAP regimen. The induction chemotherapy allowed remission to be achieved in 78.1% of cases (against 40% with standard intraperitoneal therapy), the stan- dard volume of surgical treatment was performed in 28 (87.5%) patients (21 (70%) receiving the control regime); with the use of PAFC, the size of minimum residual tumour (less than 1 cm) was achieved in 81.3% versus 63.3% with standard intraperitoneal chemotherapy. This treatment enables the use large-dose chemotherapy regimens that cause no severe systemic toxic reactions. The method is highly-effective, low-toxic and may be recommended for the treatment of patients with the ascitic form of Stages III—IV ovarian cancer.